The Correlation Between the Molecular Heterogeneity of Prolactin and Autoantibody and Complement Levels in Patients with Systemic Lupus Erythematosus - Kusworini HANDONO; Olivia ANGGRAENY; Catur Suci SUTRISNANI; Ermin RACHMAWATI; Agustina Tri ENDHARTI; Maimun Zulbaidah ARTHAMIN1 (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate the relationship between the molecular heterogeneity of prolactin (PRL) and anti-doublestranded deoxyribonucleic acid (anti-dsDNA), anti-C1q, and complement 3 (C3) levels in patients with systemic lupus erythematosus (SLE). Patients and methods: This study included 30 premenopausal females with SLE from the Rheumatology Clinic of Doctor Saiful Anwar General Hospital in Malang, Indonesia and 30 healthy females as the control group. Prolactin heterogeneity (small and large) was determined using the ultra filtration method and electrochemiluminescence immunoassay, while the total PRL, anti-dsDNA, anti-C1q, and C3 serum levels were measured by enzyme-linked immunosorbent assay. Results: The mean total PRL and small PRL serum levels for the SLE patients were 13.83±8.78 ng/mL and 4.45±1.88 ng/mL, respectively, whereas they were 9.14±3.85 ng/mL and 2.49±0.29 ng/mL, respectively for the healthy controls, indicating a significant difference between the groups (p=0.01 and p=0.00, respectively). Significant correlations were found between the small PRL serum levels and the anti-dsDNA (r=0.978; p=0.00) and C3 (r= -0.970; p=0.00) levels. Conclusion: The activity disease of SLE patients was correlated with the level of small PRL but not with total PRL.